Endoscopic Retrograde Mastoidectomy - A Review on Its Postoperative/Functional Outcome on Hearing - Meenaxi P Mehta, S. Mohammed Siddique, (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Endoscopic retrograde mastoidectomy with cartilage reconstruction has a better success rate in the treatment of limited cholesteatoma. Objective: To prepare cartilage graft from tragus and to compare pre-operative and Post-operative hearing. Methods: 35 patients with limited cholesteatoma, without intra/extra cranial complications disease were made to undergo endoscopic retrograde mastoidectomy with cartilage tympanoplasty. The study was conducted both retrospectively and prospectively. Results: In this technique, patients had an average improvement in hearing upto 10-12dB.The mean post-operative period follow up was 2-6 months. Conclusion: If endoscopic mastoidectomy is done accurately, endoscopic retrograde mastoidectomy with cartilage tympanoplasty appears to provide better success rates and hearing results.